Impact of rain-shelter cultivation on rhizosphere microecology and kiwifruit quality - Lan, Jianbin; Dong, Xixi; He, Rui; Huang, Qin; Liu, Linyu; Liu, Junlan; Tian, Ailin; Zhang, Haodan; Sun, Guoqing; Luo, Bangzhou; Zeng, Yinqiu; Li, Qiang (Frontiers in Microbiology, 2025)
The effects of kiwifruit rain shelter cultivation on the microecological characteristics of the rhizosphere soil and fruit yield and quality remain uncertain. Therefore, we compared the differences in rhizosphere soil physicochemical properties, microbial populations, enzyme activities, microbial biomass, and fruit yield and quality between kiwifruit rain shelter and open-field cultivation. Additionally, correlations among these parameters were determined. Compared with open-field cultivation, rain-shelter cultivation significantly increased kiwifruit yield (5.17–9.30%), single fruit weight (5.44–6.54%), fruit longitudinal diameter (3.75–4.08%), and transverse diameter (4.58–5.08%), and improved fruit quality, including soluble solids content (9.03–10.05%), soluble sugar content (2.41–4.55%), sugar-to-acid ratio (15.07–20.45%), and vitamin C content (19.03–20.22%). Moreover, rain-shelter kiwifruit cultivation significantly enhanced soil nutrient availability, microbial population, enzyme activities, and electrical conductivity, whereas soil total nutrient and organic matter contents decreased significantly. Further analysis revealed that kiwifruit yield and quality were significantly and positively correlated with available soil nutrients, microbial population, enzyme activities, and microbial biomass carbon and nitrogen but were negatively correlated with the carbon/nitrogen ratio of microbial biomass. These findings indicate that soil microbes and enzymes regulate kiwifruit yield and quality by influencing nutrient availability. Our study provides a firm scientific basis for the efficient soil management and conservation of kiwifruit production, thereby emphasizing the potential of rain shelter cultivation to promote sustainable agriculture.